INTERNALIZING THE VALUE OF RELIGIOUS MODERATION IN THE ERA OF DIGITAL TRANSFORMATION - Azka Budi Fauzani; Ainiyatul Jannah; Ratu Balqhis Anggun Maulan Aulia (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Religious moderation is a way of viewing religion that is wastiyyah, (not extreme), both extreme right and left. Indonesia's diversity is something that cannot be denied or abolished, religious moderation is an important thing in uniting existing diversity. Moreover, in the digital era it is necessary to convey the value of religious moderation in the digital public realm. the circulation of platforms on social media, and knowing the values of religious moderation that are implemented in the era of digital disruption. In this research, how to transform the phenomenon of preaching religious moderation to millennials from the conventional era to the digital era. The research method used in this research is library research or library research, namely research that examines a lot of literature in the form of references to books, journals, and research results. The data collection technique used is observation (observation). The analysis used is content. This research wants to examine the basic verses of the Koran that can be applied in everyday life regarding the application of religious moderation. As well as wanting to transform how the spread of dakwah follows the development of digital disruption. This research also shows the importance of digital media as a platform for spreading positive content, especially regarding religious moderation. It is time for several forms of spreading the value of religious moderation to transform from conventional to digital, oral to visual, offline preaching to online, virtual world preaching to the real world. The development of the times demands the spread of religious moderation that is more interesting, modern and creative, not inferior to the times. The main targets for spreading religious moderation are millennials because they have a close relationship with the digital world